Computational methods for fracture in porous media : isogeometric and extended finite element methods - Borst, Rene de (Elsevier, 2018)
Computational Methods for Fracture in Porous Media: Isogeometric and Extended Finite Element Methods provides a self-contained presentation of new modeling techniques for simulating crack propagation in fluid-saturated porous materials. This book reviews the basic equations that govern fluid-saturated porous media. A multi-scale approach to modeling fluid transport in joins, cracks, and faults is described in such a way that the resulting formulation allows for a sub-grid representation of the crack and fluid flow in the crack. Interface elements are also analyzed with their extension to the hydromechanical case. The flexibility of Extended Finite Element Method for non-stationary cracks is also explored and their formulation for fracture in porous media described. This book introduces Isogeometric finite element methods and its basic features and properties. The rapidly evolving phase-field approach to fracture is also discussed. The applications of this book's content cover various fields of engineering, making it a valuable resource for researchers in soil, rock and biomechanics.